History of cognitive neuroscience - Bennett, M. R.; Hacker, P. M. S. (Peter Michael Stephan) (Hoboken, N.J. : Wiley-Blackwell ; Chichester : John Wiley [distributor], 2012)
History of Cognitive Neuroscience documents the major neuroscientific experiments and theories over the last century and a half in the domain of cognitive neuroscience, and evaluates the cogency of the conclusions that have been drawn from them. Provides a companion work to the highly acclaimed Philosophical Foundations of Neuroscience - combining scientific detail with philosophical insightsViews the evolution of brain science through the lens of its principal figures and experimentsAddresses philosophical criticism of Bennett and Hacker's previous bookAccompanied by more than 100 illustration.
4.1. Introduction: Psycholinguistics and the Neuroanatomy of Language -- 4.2. The Theory of Wernicke/Lichtheim -- 4.2.1. Introduction: Wernicke -- 4.2.1. 1 Images of sensations -- 4.2.1. 2 Movement images -- 4.2.1. 3 Voluntary movement -- 4.2.1. 4 Sound images and language -- 4.2.1. 5 Language acquisition, words and concepts -- 4.2.2. Lichtheim's concept centre -- 4.2.3. Concepts and representations -- 4.2.4. Conclusion -- 4.3. The Mental Dictionary and its Units: Treisman -- 4.4. The Modular Study of Word Recognition and Reading Aloud: Morton -- 4.4.1. The model system -- 4.4.2. The cognitive system -- 4.4.3. Thought units.
Print version record.
Keywords: Cognitive neuroscience -- History; Cognitive neuroscience -- Research -- History; Electronic books